2020
DOI: 10.1177/0025817220930552
|View full text |Cite
|
Sign up to set email alerts
|

The silent deaths of the elderly in long-term care facilities during the Covid-19 pandemic: The role of forensic pathology

Abstract: The Covid-19 pandemic is currently a major global public health problem. We know that the elderly and people with chronic diseases contract the infection more easily and they develop clinically more serious and often lethal forms. To date, the reasons for this have been generically attributed to old age and underlying diseases. Most Covid-19 deaths occurred in long-term care facilities because the residents are elderly people with chronic illness living in close contact. Therefore, facilities have bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Most COVID-19-related deaths have occurred in long-term care facilities, where patients with dementia are a significant part of the residents and require close contact for assistance in their daily care (Blackman et al, 2020;Cordasco et al, 2020). Blackman et al (2020) reported the rapid evolution of COVID-19 in a longterm care facility with 150 beds for individuals with dementia, where despite the preventive measures developed, within 3 weeks of the first confirmed COVID-19 case, 30 residents had died and more than 50 were confirmed cases or were having symptoms compatible for the disease.…”
Section: Covid-19 Indirect Effects In Patients With Dementiamentioning
confidence: 99%
“…Most COVID-19-related deaths have occurred in long-term care facilities, where patients with dementia are a significant part of the residents and require close contact for assistance in their daily care (Blackman et al, 2020;Cordasco et al, 2020). Blackman et al (2020) reported the rapid evolution of COVID-19 in a longterm care facility with 150 beds for individuals with dementia, where despite the preventive measures developed, within 3 weeks of the first confirmed COVID-19 case, 30 residents had died and more than 50 were confirmed cases or were having symptoms compatible for the disease.…”
Section: Covid-19 Indirect Effects In Patients With Dementiamentioning
confidence: 99%
“…The 149 publications came from the following 26 countries: 52 from the USA [ 16 , 18 , 24 , 30 , 31 , 39 , 42 , 49 , 51 , 52 , 56 , 57 , 59–62 , 73 , 77–80 , 83 , 85 , 91–93 , 95–98 , 100 , 103 , 104 , 107–112 , 115 , 117–119 , 123 , 135 , 143 , 144 , 149 , 152 , 157 , 160 , 162 ], 13 from China [ 36 , 72 , 102 , 105 , 120 , 137–139 , 147 , 153 , 154 , 163 , 164 ], 13 from Italy [ 26 , 33 , 34 , 40 , 41 , 43 , 55 , 58 , 121 , 131 , 141 , 146 , 148 ], ten from the United Kingdom [ 21 , 29 , 44 , 48 , 63 , 89 , 113 , 130 , …”
Section: Resultsmentioning
confidence: 99%
“…Of relevance here, rapidly changing information and public health measures in relation to COVID-19 can heighten feelings of uncertainty about the future. Carers of people with dementia living in long-term care facilities may also experience increased uncertainty about the future as a result of visitation bans and disproportionately high rates of infection and death in long-term care residents worldwide 25 , 42 . Worsened carer mental health since the outbreak of COVID-19 was also associated with greater loneliness.…”
Section: Discussionmentioning
confidence: 99%